GAMIFICATION-ASSISTED FLIPPED LEARNING IN EFL READING CLASSROOM: A CASE OF SECONDARY SCHOOL IN INDONESIA - Riani Noor Yoshania; Fazri Nur Yusuf; Hanna Sundari (Indonesian EFL Journal)
World Bank's report in Program for International Student Assessment, found that during the first four years of school closures in Indonesia due to the Covid-19 pandemic, school students experienced an 11-point decline in reading skills and learning outcomes. This research focused on gamification-assisted flipped classrooms and how they improved EFL students' reading comprehension. A total of 20 third-year students from a secondary school were chosen purposefully as research participants, since they had the required characteristics. This research designed for qualitative data collection and analysis methodologies in a case study. The learning outcome scores obtained from tests that include questions about micro and macro reading comprehension skills revealed, the average score of pretest was 54, and the post-test was 87, this indicated that gamification assisted-flipped classrooms improved learning reading comprehension skills. According to findings of interviews, questionnaires and observation based on the Technology Acceptance Model regarding students' perceptions of gamification-assisted flipped classrooms, has a relatively high acceptance scale in terms of perceived usefulness, perceived ease of use, behavioral intention, and actual usage. The perceived usefulness has the highest scale, 85.82% of students believe that using Gamification in a flipped classroom improved their performance in reading comprehension. Further research is needed to determine the gamified flipped classrooms can be utilized to improve other english skills.